2020
DOI: 10.3390/nu12051322
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Human Milk on Necrotizing Enterocolitis: A Systematic Review and Meta-Analysis

Abstract: Background. Premature infants receiving breastfeed have a lower incidence of NEC than those fed preterm formula. This study aimed: (1) to update a systematic review and meta-analyses to evaluate the relationship between feeding and necrotizing enterocolitis (NEC) in low weight premature infants; (2) to conduct meta-regression analyses by subgroups; (3) to describe geographical distribution of milk banks in the world. Methods. Papers included in the meta-analysis were updated as of June 2019. Relative risks wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(96 citation statements)
references
References 65 publications
(113 reference statements)
3
85
0
8
Order By: Relevance
“…The therapeutic potential of the current findings was revealed by our identification of the AHR ligand A18 to prevent NEC when fed to mice during pregnancy, and by showing its ability to reduce TLR4 signaling in human bowel ex vivo. In view of the fact that the absence of breast milk is a major risk factor for NEC [35][36][37][38] , these findings suggest the possibility that the development of NEC may reflect impaired AHR signaling in the neonatal intestine, and also show that strategies to enhance the delivery of AHR ligands either directly to the neonate, or secondarily through the mother, may offer new strategies for the prevention or treatment of NEC.…”
Section: Discussionmentioning
confidence: 91%
“…The therapeutic potential of the current findings was revealed by our identification of the AHR ligand A18 to prevent NEC when fed to mice during pregnancy, and by showing its ability to reduce TLR4 signaling in human bowel ex vivo. In view of the fact that the absence of breast milk is a major risk factor for NEC [35][36][37][38] , these findings suggest the possibility that the development of NEC may reflect impaired AHR signaling in the neonatal intestine, and also show that strategies to enhance the delivery of AHR ligands either directly to the neonate, or secondarily through the mother, may offer new strategies for the prevention or treatment of NEC.…”
Section: Discussionmentioning
confidence: 91%
“…Such racial disparities in prenatal care are important as several maternal factors have been associated with NEC, including premature rupture of membranes ( 31 ), chorioamnionitis ( 32 ), intrauterine growth restriction ( 33 ), placental abruption ( 34 ), and inadequate antenatal steroid administration for possible pre-term delivery ( 35 ). In another study, Kogan et al ( 36 ) analyzed racial disparities in prenatal care and found that non-Hispanic Black women were more likely to report not receiving advice about important topics such as breastfeeding – a well-known protective mediator in NEC ( 37 ). Several studies have also identified inequality in the care of very low birth weight infants by race, with non-Hispanic Black and Hispanic infants receiving care at lower-quality hospitals compared to non-Hispanic White infants ( 38 41 ).…”
Section: Possible Explanations For Racial Disparities In Necmentioning
confidence: 99%
“…Evidence of the protective role of human milk (HM) against NEC in preterm infants is robust [ 2 , 3 , 4 , 5 ]. In recent years, the role of probiotic administration in preventing NEC has been also investigated through observational studies and randomized controlled trials (RCTs), whose results have been summarized in numerous systematic reviews and meta-analyses [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%